Centella asiatica Activities towards Staphylococcus aureus and Escherichia coli Growth - Sandi Murdiyansah; Dewa Ayu Citra Rasmi; I Gde Mertha (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
Centella asiatica contains some secondary metabolic compounds, e.g. tannin, alkaloid, flavonoid, saponin, and triterpenoid, known as medicinal plants as well, one of which is as a anti-bacterial. The present study aimed at examining the activities of Centella asiatica extract towards the growth of Staphylococcus aureus and Escherichia coli. The extraction of C. asiatica was done by using ethanol and ethyl acetate solvents and the activity test employed seaweed diffusion. The hindrance power of Centella asiatica extract was tested in 30%, 50%, and 95% and the data were analyzed qualitatively with the standard issued by the Clinical and Laboratory Standard Institute and quantitatively with ANOVA. It shows that Centella asiatica extract in the ethyl acetate can hinder the growth of Staphylococcus aureus in the acetate concentration of 50% and 70% at the sensitive level and Escherichia coli at the intermediate level in the extract concentration of 50% and 70%. However, Centella asiatica activities in the ethanol solvent hinders the growth of either Centella asiatica or Escherichia coli with resistant category in the extract concentration of 70%. The hindrance power of Centella asiatica extract in ethyl acetate in the growth of Staphylococcus aureus is significantly more effective than that of Centella asiatica extract in the ethanol solvent